Case report: Urothelial injury in a female with breast cancer: a rare adverse event after the combination of paclitaxel and trastuzumab - Cao, Tinghua; Duan, Zhipei; Zhu, Jing; Wu, Jing; Chen, Jun; Jiang, Mingjun; Lu, Xialiang; Li, Yan (Frontiers in Oncology, 2024)
Several breast cancer (BC) patients showed urinary tract infection after adjuvant trastuzumab plus paclitaxel, but no case of urothelial injury has been reported. In this case, we report a 47-year-old female patient with stage I invasive ductal carcinoma in the left breast presenting with urothelial injury after the combination of trastuzumab and paclitaxel. Initially, the patient was highly suspected with urinary tract infection as she showed abdominal and low back pain, as well as urinary irritation symptoms and hematuria. Unfortunately, the conditions were not attenuated after anti-infection therapy.Contrast enhanced CT showed extensive exudation and edema in bilateral renal pelvis, ureter, and bladder, together with dilatation and effusion in renal pelvis and ureter.Cystoscopy showed extensive congestion, edema and erosion in bladder epithelium.Pathological analysis demonstrated slight thinning or even loss in the uroepithelial cell layer, and interstitial congestion. In addition, there was growth arrest in the epithelial cells. Immunohistochemistry indicated HER2 expression in the urothelial cells. Finally, the patient was diagnosed with urothelial injury after combination of paclitaxel and trastuzumab. The symptoms were spontaneously cured with no administration of any antibiotics in the three-month follow-up.